2022
DOI: 10.1080/23802359.2022.2040391
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Chimonobambusa angustifolia C. D. Chu et C. S. Chao, a fiber and bamboo shoot species in Poaceae

Abstract: Chimonobambusa angustifolia is a famous ornamental and edible bamboo species. Here, the complete chloroplast (cp) genome of C. angustifolia was assembled and annotated. The cp genome is 139,611 bp in size, consisting of two copies of inverted repeat (IR) regions of 21,799 bp, one large single-copy (LSC) region of 83,202 bp, and one small single-copy (SSC) region of 12,811 bp. It encodes 133 genes (110 unique), including 86 protein-coding genes (77 unique), 39 tRNA genes (29 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 2021 ; Xu et al. 2022 ) have been reported: C. hejiangensis , C. sichuanensis , and C. angustifolia . In this study, we reported a new chloroplast genome of this genus ( C. luzhiensis ), which will contribute to the genetic and conservation research of this plant.…”
mentioning
confidence: 99%
“… 2021 ; Xu et al. 2022 ) have been reported: C. hejiangensis , C. sichuanensis , and C. angustifolia . In this study, we reported a new chloroplast genome of this genus ( C. luzhiensis ), which will contribute to the genetic and conservation research of this plant.…”
mentioning
confidence: 99%